Revealing The Spatial Matter in Indonesia’s Economic Growth Model: A Cross-Province Analysis - Santoso, Edy; Annegrat, Ahmed Mohamed; Priyono, Teguh Hadi; Lestari, Endah Kurnia; Kusumawardhani, Vebry Eka (ETIKONOMI, 2026)
Research Originality: This research integrates spatial econometric modeling to analyze the determinants of Indonesia's economic growth, highlighting the influence of spatial dependence on neighboring regions. It uses spatial models to provide insights into Indonesia's growth dynamics from a geographically interdependent perspective. Research Objectives: Examine the key factors driving Indonesia's economic growth by incorporating internal regional elements and external spatial influences from neighboring provinces. Research Method: This study employs a spatial econometric approach to analyze Indonesia’s economic growth across 34 provinces from 2015 to 2024. Empirical Results: The empirical analysis confirms the presence of spatial dependence in regional economic growth, with neighboring provinces influencing one another. Foreign Direct Investment (FDI), Domestic Direct Investment (DDI), and population significantly impact growth directly and through spillovers. However, road infrastructure has an insignificant effect. Implications: This research emphasizes the importance of provincial collaboration on investment, infrastructure, and trade. While population growth matters, skill enhancement is crucial for development. Policymakers should prioritize high-quality infrastructure and leverage spatial data to promote balanced growth and reduce regional disparities. JEL Classification: C33, O16, O18, R11